2008
DOI: 10.1291/hypres.31.335
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin Slows the Progression of Cardiac Remodeling in Mice with Pressure Overload and Inhibits Epidermal Growth Factor Receptor Activation

Abstract: The aim of this study was to investigate whether atorvastatin inhibits epidermal growth factor receptor

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 42 publications
0
21
0
1
Order By: Relevance
“…ADAM-12 is pathologically expressed in the heart during the development and progression of cardiac hypertrophy, parallel with other developmental and fetal genes such as α-skeletal actin and β-myosin heavy chain [22]. Agonist activation of ADAM-12 is thought to mediate the development of cardiac hypertrophy, as pharmacological ADAM-12 inhibition attenuates cardiac hypertrophy but causes no attenuation of the severity of the hypertension [96,97]. In response to GPCR agonists and pressure overload, ADAM-12 sheds HB-EGF in the myocardium promoting the development of cardiac hypertrophy [96,97].…”
Section: Mmps and Adams In Models Of Hypertensive Cardiac Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…ADAM-12 is pathologically expressed in the heart during the development and progression of cardiac hypertrophy, parallel with other developmental and fetal genes such as α-skeletal actin and β-myosin heavy chain [22]. Agonist activation of ADAM-12 is thought to mediate the development of cardiac hypertrophy, as pharmacological ADAM-12 inhibition attenuates cardiac hypertrophy but causes no attenuation of the severity of the hypertension [96,97]. In response to GPCR agonists and pressure overload, ADAM-12 sheds HB-EGF in the myocardium promoting the development of cardiac hypertrophy [96,97].…”
Section: Mmps and Adams In Models Of Hypertensive Cardiac Diseasementioning
confidence: 99%
“…Agonist activation of ADAM-12 is thought to mediate the development of cardiac hypertrophy, as pharmacological ADAM-12 inhibition attenuates cardiac hypertrophy but causes no attenuation of the severity of the hypertension [96,97]. In response to GPCR agonists and pressure overload, ADAM-12 sheds HB-EGF in the myocardium promoting the development of cardiac hypertrophy [96,97]. ADAM-12 also cleaves insulin-like growth factor binding protein, releasing insulin-like growth factor which then activates the insulin-like growth factor receptor, potentially contributing further to hypertrophic growth in the heart [98].…”
Section: Mmps and Adams In Models Of Hypertensive Cardiac Diseasementioning
confidence: 99%
“…Slowing or reversing cardiac remodeling is an important therapeutic goal in patients with CHF. Studies have shown that hydroxymethylglutaryl-CoA reductase inhibitors (statins) attenuate cardiac remodeling in animals or patients with either ischemic or non-ischemic CHF (1)(2)(3)(4)(5)(6)(7), suggesting that statin therapy may be a potential novel approach for CHF. A meta-analysis of randomized controlled trials showed that treatment with statins in CHF patients attenuates cardiac remodeling and relives clinical symptoms (8).…”
Section: Introductionmentioning
confidence: 99%
“…In response to a number of inhibitory (stress) signals, the activity of eIF2B, and thus the rate of assembly of ternary complex, is reduced, which can lead to the repression of global rates of protein synthesis. Intriguingly, there have been a number of reports indicating that statins attenuate or prevent cardiac hypertrophy (5,20,24,43). In this context, it is important to note that eIF2B⑀ is implicated in ␤-adrenergic mediated cardiomyocyte hypertrophy (12) and that overexpression of eIF2B⑀ increases GEF activity and/or protein synthesis in a number of different cell types (3,12,35,40,42).…”
mentioning
confidence: 99%